2011
DOI: 10.1245/s10434-011-2062-z
|View full text |Cite
|
Sign up to set email alerts
|

Lymphovascular Invasion is a Significant Prognosticator in Rectal Cancer Patients Who Receive Preoperative Chemoradiotherapy Followed by Total Mesorectal Excision

Abstract: Positive LVI had a negative impact on survival in patients with rectal cancer who received preoperative CRT and TME and is significantly associated with an increased chance of distant recurrence. Based on this finding, more tailored adjuvant chemotherapy is warranted for advanced rectal cancer patients with LVI to reduce the distant dissemination of tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 28 publications
3
24
3
Order By: Relevance
“…The majority of researchers tend to consider angioinvasion as an adverse risk factor for LR (18). However, this is inconsistent with the follow-up data recorded by Lee et al , although a significant difference was observed between distant metastasis and overall survival (19). …”
Section: Recurrent Risk Factors Following Primary Tumor Resectioncontrasting
confidence: 82%
“…The majority of researchers tend to consider angioinvasion as an adverse risk factor for LR (18). However, this is inconsistent with the follow-up data recorded by Lee et al , although a significant difference was observed between distant metastasis and overall survival (19). …”
Section: Recurrent Risk Factors Following Primary Tumor Resectioncontrasting
confidence: 82%
“…11,26 Two studies found no impact of PNI on OS in multivariate analysis, although both found an impact of PNI on OS in univariate analysis, and both studies evaluated PNI as a single variable not combined with LVI. 24,25 In our study, we may not have been able to fully evaluate the impact of PNI on OS due to censoring of patients, limited follow-up, and few observed events ( P = 0.15).…”
Section: Discussionmentioning
confidence: 89%
“…Six studies in addition to ours found PNI to be significant for DFS on multivariate analysis. 1113,23,24,26 Of note, PNI was combined with lymphovascular invasion (LVI) as a single variable in the multivariate analysis in 2 studies. 11,26 Also, 2 studies did not find PNI to be correlated with DFS on multivariate analysis 22,25 ; however, in one of these studies, 25 PNI was correlated with DFS on univariate analysis ( P < 0.001), and the P -value was close to being significant ( P = 0.051) on multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Age, gender, TNM stage, venous invasion, tumour necrosis, peri-tumoural lymphocytic infiltration, tumour budding and CEA levels were also independently associated with poor survival in at least some studies [17,18,21,22,26,30,32,33,39].…”
Section: Discussionmentioning
confidence: 96%